The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1993
DOI: 10.1021/ef00038a013
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic degradation studies of a coal-derived and a petroleum-derived aviation jet fuel

Abstract: The future high-Mach aircraft requires advanced jet fuel with high stability in rigorous thermal environments. In this work high-temperature thermal stability of two JP-8 type jet fuels, a petroleumderived JP-8P and a coal-derived JP-8C was studied by stressing in closed reactors at 450 °C under 0.7 MPa of N2 for periods ranging from 0.5 to 16 h. The extents of fuel degradation in terms of liquid depletion, gas formation, and solid deposition were always higher with JP-8P than with JP-8C.There appeared an indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 0 publications
5
106
0
Order By: Relevance
“…This is similar to results found for the coal-derived jet fuel JP8C at these temperatures and times. [5] However, gas formation is slightly higher than that observed from JP8C but still lower than that from the petroleum-derived jet fuel JP8P. [9] This indicates that the high content of cycloalkanes most likely prevents the formation of solids, whereas the relatively large concentration of linear/branched alkanes, such as in petroleum-derived JP8P, leads to a more dominant gas production when compared with the coal-derived jet fuel JP8C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to results found for the coal-derived jet fuel JP8C at these temperatures and times. [5] However, gas formation is slightly higher than that observed from JP8C but still lower than that from the petroleum-derived jet fuel JP8P. [9] This indicates that the high content of cycloalkanes most likely prevents the formation of solids, whereas the relatively large concentration of linear/branched alkanes, such as in petroleum-derived JP8P, leads to a more dominant gas production when compared with the coal-derived jet fuel JP8C.…”
Section: Resultsmentioning
confidence: 99%
“…A volume of 5 ml was used, which was charged into a microautoclave with a total volume of 25 ml. [5] To remove entrapped air, the system was degassed 6 times with 1000 psi of ultra-high-purity N 2 (99.999%).…”
Section: *2 Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported the effects of trace amounts of sulfur and nitrogen compounds and other contaminants such as metals [35,36], because these elements were found in large concentrations in deposits compared to fresh fuels [25]. A recent study reported that nitrogen and sulfur compounds were presented only in the liquid-phase product, but not in the solid phase deposits, and indicated that they did not aggregate during solid formation [34].…”
Section: Formation Of Solid Depositsmentioning
confidence: 99%
“…To meet the fuel performance and compositional specifications for diesel fuel, it is necessary for both RCO and LCO to be hydrogenated [43,44]. This work focuses on the development of increasingly sulfur-tolerant, noble-metal catalysts for the lowtemperature hydrotreating and dearomatization (LTHDA) of distillate fuels for the production of ultra-clean and low-aromatic diesel fuels.…”
Section: Subtask 32 Saturation Of Two-ring Aromaticsmentioning
confidence: 99%